Eco-friendly strategies for spice production through microbial inoculants - R, Praveena; Srinivasan, V; Kumar, C M Senthil; Sarathambal, C; C N, Biju; B, Manimaran; R, Dinesh (Indian Horticulture, 2025)
The growing emphasis on residue-free spices and environmentally sustainable agriculture has driven the need for eco-friendly alternatives to conventional chemical inputs. This study underscores the crucial role of microbial inoculants in spice cultivation, functioning as biofertilizers, biopesticides, and biocontrol agents. Beneficial microbes such as Trichoderma spp., Bacillus licheniformis,Pochonia chlamydosporia, and various PGPR strains have proven effective in suppressing diseases, enhancing nutrient availability, and promoting plant growth in crops like ginger, turmeric, cardamom, and black pepper. Integrating these microbial tools not only boosts crop productivity and resilience but also ensures compliance with stringent international standards, thereby supporting sustainableand export-oriented spice production.